2014
DOI: 10.2459/jcm.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between arterial stiffness and diastolic function

Abstract: An independent association between grade I left ventricular diastolic dysfunction and increased arterial stiffness is demonstrated at the earliest stage of heart failure. Hence, assessment of vascular function, beyond cardiac function, should be included in a comprehensive clinical evaluation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
(60 reference statements)
2
17
0
2
Order By: Relevance
“…Cesare Russo et al [18] studied gender difference in arterial stiffness and its relation to diastolic function, and found general arterial stiffness to be correlated with female gender which reflected the higher incidence of diastolic dysfunction in females. Similar results correlating general arterial stiffness-as reflected by pulse wave velocity, central pulse pressure/stroke volume index, total arterial compliance, pulse pressure amplification, and augmentation indexwith diastolic function was found by Zito et al [19], Agoşton-Coldea et al [20], and Mottram et al [21].…”
Section: Discussionsupporting
confidence: 83%
“…Cesare Russo et al [18] studied gender difference in arterial stiffness and its relation to diastolic function, and found general arterial stiffness to be correlated with female gender which reflected the higher incidence of diastolic dysfunction in females. Similar results correlating general arterial stiffness-as reflected by pulse wave velocity, central pulse pressure/stroke volume index, total arterial compliance, pulse pressure amplification, and augmentation indexwith diastolic function was found by Zito et al [19], Agoşton-Coldea et al [20], and Mottram et al [21].…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies investigated possible association of both arterial stiffness and pulse pressure with left ventricular diastolic dysfunction in hypertensive patients [32,33]. In particular, Mottram et al [32] observed an independent [18].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, there is an increasing interest for an extensive evaluation of stiffness parameters, particularly in patients at major risk. Recently, new radio frequency based software has been introduced, as alternative approach over conventional method, for assessing local arterial stiffness in clinical routine [9][10][11][12][13]. However, in our knowledge, studies investigating the relation between arterial stiffness, by echo-tracking systems, and plaque composition are lacking to date.…”
Section: Discussionmentioning
confidence: 99%